PENGARUH PENDEKATAN SAINTIFIK TERHADAP KUALITAS BELAJAR SISWA KELAS VIII MTS BABUSSALAM BATU KARANG KECAMATAN SIMPANG KANAN KABUPATEN ACEH SINGKIL - Alpian, Alpian (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
Class VIII students of MTs Babussalam so far, learning is still carried out with the conventional approach of learning through explanations and namely question and answer, this does not create critical, creative and scientific students, so that students are more qualified, learning with a scientific approach needs to be applied, in that the writer wants to apply and indicators of whether the scientific approach can form quality students, or whether the scientific approach can affect the quality of student learning so that with the scientific approach students are better able to reason, understand and analyze problems in learning. This is the rationale for the author to conduct deeper research. The formulation of the problem in this study is how the learning quality of class VIII students of MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency. how is the scientific approach in the teaching and learning process carried out in class VIII MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency. Is there an effect of scientific learning on the learning quality of class VIII students of MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency. Based on the results of the research, the learning quality of class VIII students at MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency has a good learning quality, this can be seen from the students' ability to take part in the teaching and learning process with a scientific approach. Science in the teaching and learning process carried out in class VIII MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency is through a scientific approach, a thinking power development approach, approaches and hypotheses and the ability to present problems and finally the ability to draw conclusions on existing problems. The effect of scientific learning on the learning quality of class VIII students of MTs Babussalam Batu Karang, Simpang Kanan District, Aceh Singkil Regency, because with a scientific approach it can improve critical thinking skills, scientific thinking, problem analysis and identification skills, data and the ability to take resources owned by students.